STAGES OF MINERALIZATION AND LOCALIZATION FACTORS OF THE AGYURT GOLD-COPPER-MOLYBDENUM DEPOSIT (LESSER CAUCASUS, AZERBAIJAN) - Kerimli, U. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article considers the stages of mineralization of the Agyurt gold-copper-molybdenum deposit of the Lesser Caucasus. The following mineralization stages were established at the field: 1) quartz-molybdenum; 2) quartz-pyrite-chalcopyrite with gold; 3) quartz-carbonate-sphalerite; 4) quartz-carbonate. Gold ore bodies are mainly composed of aggregates of the second stage of mineralization, which is productive. Its mineral substance is represented by three paragenetic associations: 1) quartz-pyrite; 2) calcite-chalcopyrite-marcasite; 3) gold-telluride-bismuth. Chemical analyzes of pyrites, bismuthin, tellurium bismuthite are given. It has been found that native gold is found in the form of small, simple forms of gold in grains of early pyrite. In veins of chalcopyrite and grains of pyrite, it is usually confined to the marginal parts. The largest amount of gold is in close intergrowth with tellurium-bismuth minerals. It was found that the ore deposition environment (mineral composition, chemistry and structural and texture features of the host rocks) played a decisive role for various types of mineralization. It is established that, in the plan, the Agyurt deposit is localized in the contour of a rock block elongated in the northwest (submeridional) direction, bounded by tectonic zones from the north-north-west and north-east, which also bear a certain imprint of the formation of the structural plan of the ore field with near latitudinal strike of tectonic elements. These structures are most tectonically prepared for the localization of gold-copper-molybdenum mineralization (updated in the pre-ore stages and most permeable for hydrothermal structures), and were the main ore-supplying and ore-locating structural elements. The ore zones represented by hydrothermal-metasomatic formations, as well as quartz veins piercing them and numerous veinlets and sometimes mineralized dykes, are controlled by the Main Ordubad longitudinal (280°∠70–80°NE) and Agyurt-Misdag transverse (40–50°∠70° NE) with discontinuous violations and adjoin the hanging side (northeast flank) of the first. The combination of structural and petrogenetic factors not only predetermined the formation of deposits of the Agyurt type, but also determined the horizontal and vertical zonation of mineralization: an increase in the Mo content and a decrease in Cu with depth are established. The same pattern is observed in the horizontal direction: as you move away from the intrusive massif and the ore-removing channel, there is a transition from Cu-Mo-mineralization to copper and then polymetallic, i.e. the role of Cu increases, then Pb and Zn. The horizontal zoning in Agyurt is expressed in an increase in Au content and the total amount of sulfides with distance from the Main Ordubad Fault, and vertical shows an increase in Au content and decreases in Ag with depth.
Keywords: Agyurt gold-copper-molybdenum deposit; Lesser Caucasus; stages of mineralization; localization factors